PEMANFAATAN MEDIA DALAM PEMBELAJARAN PAI DI SMPN 3 SAMATIGA - Fedry Saputra (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2021)
The media used by the teacher is still very simple, because the school is newly built, there is a lack of necessary learning facilities, including very limited teaching aids. Based on the background that the author raised above, the formulation of the problem is as follows: (1) What forms of media are used in learning Islamic Religious Education at SMPN 3 Samatiga (2) What factors support the use of media in PAI learning at SMPN 3 Samatiga? This research method uses a qualitative approach with descriptive research methods. The results of the research are: (1) The use of learning media at SMPN 3 Samatiga is as follows: the use of picture chart media, the use of blackboard media, the use of print media, the use of the Koran practical demonstration media, and the use of murattol tapes. (2) Supporting factors: the willingness and readiness of students and a sense of enthusiasm for students to accept learning using media, including the student learning environment, participation of parents and school equipment, Inhibiting factors: limitations and lack of variety of educational media used in the learning process.